2002
DOI: 10.1046/j.1472-765x.2002.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Saccharomyces cerevisiae and Kloeckera apiculata strains from Aglianico wine

Abstract: Aims: Kloeckera apiculata and Saccharomyces cerevisiae yeast species are dominant, respectively, at the early and at the following stages of wine fermentation. In the present study, PCR fingerprinting and NTS region amplification and restriction were applied as techniques for monitoring yeast population performing Aglianico of Vulture grape must fermentation. Methods and Results: Thirty S. cerevisiae and 30 K. apiculata strains were typed by PCR fingerprinting with (GAC)5 and (GTG)5 primers and by complete NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…MSP-PCR fingerprinting has been used to type fungal strains by several research groups. In most cases species-specific PCR patterns are obtained (17,25,29), but in some instances this approach results in intraspecific differentiation (4,18). Our results suggest that primers (GTG) 5 and M13 are useful to discriminate populations of Phaffia/ Xanthophyllomyces.…”
Section: Discussionmentioning
confidence: 99%
“…MSP-PCR fingerprinting has been used to type fungal strains by several research groups. In most cases species-specific PCR patterns are obtained (17,25,29), but in some instances this approach results in intraspecific differentiation (4,18). Our results suggest that primers (GTG) 5 and M13 are useful to discriminate populations of Phaffia/ Xanthophyllomyces.…”
Section: Discussionmentioning
confidence: 99%
“…3). Fingerprinting with this primer usually gives species-specific patterns, but there are other examples of pattern differentiation among geographically separated strains belonging to the same species (Caruso et al, 2002;Libkind et al, 2007). In spite of the different fingerprinting profiles, the identical phenotypic characteristics and the D1/D2 and ITS sequences indicate that the Oklahoman and Brazilian isolates belong to the same species.…”
mentioning
confidence: 99%
“…This is the case for the NTS region (Baleiras Couto et al, 1996;Capece et al, 2003;Caruso et al, 2002;Nguyen & Gaillardin, 1997;Pulvirenti et al, 2000), the 18S gene (Capece et al, 2003), and various domains of the 26S gene (Baleiras Couto et al, 1996Romancino et al, 2008;SmoleMozina et al, 1997;van Keulen et al, 2003). However, the absence of a sequence database for these regions means that their use cannot be generalized for the identification of yeasts.…”
Section: Restriction Analysis Of Ribosomal Dna (Rdna)mentioning
confidence: 99%
“…Studies have also been undertaken to analyze molecular variation in natural populations of S. cerevisiae using restriction analysis of mtDNA (Granchi et al, 2003;Gutiérrez et al, 1997;Pramateftaki et al, 2000;Querol et al, 1994;Sabaté et al, 1998;Torija et al, 2001), electrophoretic karyotyping (Frezier & Dubourdieu, 1992;Schü tz & Gafner, 1993, microsatellite analysis (Caruso et al, 2002;Howell et al, 2004), fluorescent in situ hybridization (FISH) (Xufre et al, 2006), or a combination of techniques (Egli et al, 1998;Ló pes et al, 2002;Nadal et al, 1996;Rodríguez et al, 2004;Torriani et al, 1999;Versavaud et al, 1995). These studies have shown that different strains of S. cerevisiae dominate fermentation in different appellations.…”
Section: Analysis Of Variation In Yeast Populations During Natural Fementioning
confidence: 99%